Novel splice isoforms for NLGN3 and NLGN4 with possible implications in autism. Issue 5 (28th April 2006) - Talebizadeh, Z; Lam, D Y; Theodoro, M F; Bittel, D C; Lushington, G H; Butler, M G
Abstract : Objective: To screen cDNA for NLGN3 and NLGN4 from lymphoblastoid cells from autistic subjects. Methods and results: 10 young autistic females and 30 non-autistic subjects were studied for alterations in two X linked genes, NLGN3 and NLGN4. A novel NLGN4 isoform lacking exon 4, which occurred de novo on the paternal allele, was identified in one of the autistic females. Monoallelic expression of NLGN4 was seen in this subject and in 11 of 14 informative autistic and non-autistic females using a single nucleotide polymorphism found at 3′ UTR. Additionally, the NLGN3 transcript was present in two isoforms (with and without exon 7) in nine of 10 autistic females and in 30 non-autistic subjects, including parents of the autistic female having only the complete transcript with exon 7, and from the whole brain of a control. The novel truncated NLGN3 product may have a regulatory role, as reported in other proteins (for example, vasopressin receptor) by attenuating the function of the full length isoform, resulting in a reduction of the mature protein. Three dimensional protein structures were characterised using comparative modelling, and significant changes were suggested in the protein cores for these two neuroligin isoforms. Conclusions: Splice variants may lead to potentially abnormal neuroligins in the causation of autism spectrum disorders.